Is aortoiliac calcification linked to colorectal anastomotic leakage? A case-control study. (January 2016) - Boersema, G.S.A.; Vakalopoulos, K.A.; Kock, M.C.J.M.; van Ooijen, P.M.A.; Havenga, K.; Kleinrensink, G.J.; Jeekel, J.; Lange, J.F.
Abstract: Background: Anastomotic leakage in bowel surgery remains a devastating complication. Various risk factors have been uncovered, however, high anastomotic leakage rates are still being reported. This study describes the use of calcification markers of the central abdominal arteries as a prognostic factor for colorectal anastomotic leakage. Methods: This case-control study includes clinical data from three different hospitals. Calcium volume and calcium score of the aortoiliac tract were determined by CT-scan analysis. Cases were all patients with anastomotic leakage after a left-sided anastomosis (n = 30). Three controls were randomly matched for each case. Only patients with a contrast-enhanced pre-operative CT-scan were included. Results: The measurements of the calcium score and calcium volume of the different trajectories showed that there was one significant difference with regard to the right external iliac artery. Multiple regression analysis showed a significant different negative odds ratio of the presence of calcium in the right external iliac artery. Conclusion: This study demonstrates that calcium volume and calcium score of the aortoiliac trajectory does not correlate with the risk of colorectal anastomotic leakage after a left-sided anastomosis. Highlights: Left-sided colon anastomoses are associated with a higher leakage risk. Correlation of abdominal atherosclerotic calcifications and leakage was investigated. No association is found between the calcium score/volume and anastomotic leakage. Visualization of the collateral network around the anastomosis may be helpful.